Overexpression of MMP13 Is Associated with Clinical Outcomes and Poor Prognosis in Oral Squamous Cell Carcinoma - Vui King Vincent-Chong; Iman Salahshourifar; Lee Peng Karen-Ng; Ming Yhong Siow; Thomas George Kallarakkal; Anand Ramanathan; Yi-Hsin Yang; Goot Heah Khor; Zainal Ariff Abdul Rahman; Siti Mazlipah Ismail; Narayanan Prepageran; Wan Mahadzir Wan Mustafa; et al. (The Scientific World Journal)
Matrix metalloproteinase 13 (MMP13) plays a central role in the MMP activation cascade that enables degradation of the extracellular matrix and basement membranes, and it is identified as a potential driver in oral carcinogenesis. Therefore, this study aims to determine the copy number, mRNA, and protein expression of MMP13 in oral squamous cell carcinoma (OSCC) and to associate these expressions with clinicopathological parameters. Copy number, mRNA, and protein expression analysis of MMP13 were determined using real-time quantitative PCR and immunohistochemistry methods in OSCC samples. The correlations between MMP13 expressions and clinicopathological parameters were evaluated, and the significance of MMP13 as a prognostic factor was determined. Despite discrepancies between gene amplification and mRNA and protein overexpression rates, OSCC cases showed high amplification of MMP13 and overexpression of MMP13 at both mRNA and protein levels. High level of MMP13 protein expression showed a significant correlation with lymph node metastasis (P=0.011) and tumor staging (P=0.002). Multivariate Cox regression model analysis revealed that high level of mRNA and protein expression of MMP13 were significantly associated with poor prognosis (P<0.050). Taken together, these observations indicate that the MMP13 protein overexpression could be considered as a prognostic marker of OSCC.